2019
DOI: 10.1002/dvdy.96
|View full text |Cite
|
Sign up to set email alerts
|

Stability and plasticity of positional memory during limb regeneration in Ambystoma mexicanum

Abstract: Background Urodele amphibians are capable of regenerating their organs after severe damage. During such regeneration, participating cells are given differentiation instructions by the surrounding cells. Limb regeneration has been investigated as a representative phenomenon of organ regeneration. Cells known as blastema cells are induced after limb amputation. In this process, dermal fibroblasts are dedifferentiated and become undifferentiated similar to limb bud cells. Just like limb bud cells, the induced bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Cell origin must have a great influence on limb morphogenesis, even though a developing limb bud and a regenerating blastema exhibit similar genetic cascades in morphogenesis. We have previously demonstrated that the gene expression pattern reflects cell origin 33 . Shh -expressing cells only emerge from posteriorly derived cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell origin must have a great influence on limb morphogenesis, even though a developing limb bud and a regenerating blastema exhibit similar genetic cascades in morphogenesis. We have previously demonstrated that the gene expression pattern reflects cell origin 33 . Shh -expressing cells only emerge from posteriorly derived cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of the re-expression of Shh or Fgf8 is predetermined by the origin of the cell. Our previous report showed that the spatial location of cells before amputation dictates gene expression in a regeneration blastema 33 . Considering this, the Shh + domain would be restricted within the area that, the posterior-derived cells occupy, under the influence of FGF8.…”
Section: Cell Memory and Shh/fgf8 Expression In Axolotl Blastemamentioning
confidence: 99%
“…Since then, many different studies have used the grafting approach to provide a further detailed understanding of evolution, development, and tissue regeneration in axolotl. 30,[44][45][46][47][48]…”
Section: Ubiquitous Fluorescent Reportersmentioning
confidence: 99%
“…Nevertheless, this study provided important insights on lineage restriction during limb regeneration. Since then, many different studies have used the grafting approach to provide a further detailed understanding of evolution, development, and tissue regeneration in axolotl 30,44‐48 …”
Section: Ubiquitous Fluorescent Reportersmentioning
confidence: 99%
“…This is not always the case, as the cnidarian Hydra can achieve regeneration with limited contribution from the proliferation of new cells [ 8 ]. Whole-body regeneration also requires the ability of the animal to reset its major body axes through positional cues, such that the correct tissues are regenerated in the correct spatial domain [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%